2010
DOI: 10.1111/j.1532-849x.2009.00562.x
|View full text |Cite
|
Sign up to set email alerts
|

Gender Differences in the Amount of Gingival Display During Smiling Using Two Intraoral Dental Biometric Measurements

Abstract: Significantly more women displayed gingiva in smiling. Men had significantly wider and longer central incisors. No differences were recorded between men and women relative to both the horizontal and vertical anterior tooth overlap. Subjects who displayed gingiva when smiling had more horizontal and vertical overlap of anterior teeth.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 37 publications
(140 reference statements)
2
9
0
Order By: Relevance
“…The results of our study show that high and average smiles are more prevalent in women than in men. Several studies have shown that men tend to have smiles that are lower or with no dental display, due to the fact that they generally have longer upper lips than women . The smile height is associated with the variables of gingival display and total gingival display, which, in this study, are higher in women than in men.…”
Section: Discussionmentioning
confidence: 44%
See 1 more Smart Citation
“…The results of our study show that high and average smiles are more prevalent in women than in men. Several studies have shown that men tend to have smiles that are lower or with no dental display, due to the fact that they generally have longer upper lips than women . The smile height is associated with the variables of gingival display and total gingival display, which, in this study, are higher in women than in men.…”
Section: Discussionmentioning
confidence: 44%
“…and Al‐Jabrah et al . , who found that men's maxillary right central incisors were wider and longer than those of women but did not observe gender differences for the central incisor width‐to‐length ratio.…”
Section: Discussionmentioning
confidence: 95%
“…The plaque score was measured using the method of Silness and Loe. The following features were noted: existence and type of restoration (healthy tooth without filling(s); composite filling(s); ceramic veneer; faceted crown; metal ceramic crown; and full ceramic crown), and fracture marks on the upper anterior teeth and crowded teeth. Subjects self‐reported the presence of bleeding gums (on a scale from 1 = never to 4 = always).…”
Section: Methodsmentioning
confidence: 99%
“…More women displayed gums than men in a 2: 1 ratio. Subjects with gingival display had significantly more horizontal and vertical overlap of anterior teeth compared to those who did not display gingivae when smiling [13]. The described study does use the dental biometrics measures, but not in the context of disease identification or dental problems of a patient.…”
Section: Medical Biometricsmentioning
confidence: 99%